MENDIDIK ANAK MENJAGA LINGKUNGAN DAN MENARUH KASIH TERHADAP SESAMA - Pranada Pranada; Intan Suriyanti; Donal Pangihutan; Feri Aman Mendrofa; Samuel Tampubolon (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Where does education begin? and when is a person appropriate to receive education? Of course, there are many answers that we can convey. But what we must understand is how important it is to convey special education to children from an early age. In this writing, Tabgha Batam Theological College also volunteered to take part in educating children and providing education related to environmental hygiene. Besides that, by cleaning up our environment as educators, we can also provide knowledge about cleaning waste, namely some that can be directly thrown into the trash, but there is also waste that can still be utilized, which means that there is waste that can still be commercialized and given to scavengers. Thus the educators also teach to love others as well as to clean and also the health of the surrounding environment.